Biological functions, mechanisms, and clinical significance of circular RNA in colorectal cancer - Fang, Guida; Xu, Dalai; Zhang, Tao; Wang, Gang; Qiu, Lei; Gao, Xuzhu; Miao, Yongchang (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is a leading cause of cancer-related death worldwide due to the lack of effective diagnosis and prognosis biomarkers and therapeutic targets, resulting in poor patient survival rates. Circular RNA (circRNA) is a type of endogenous non-coding RNA (ncRNA) with a closed-loop structure that plays a crucial role in physiological processes and pathological diseases. Recent studies indicate that circRNAs are involved in the diagnosis, prognosis, drug resistance, and development of tumors, particularly in CRC. Therefore, circRNA could be a potential new target for improving CRC diagnosis, prognosis, and treatment. This review focuses on the origin and biological functions of circRNA, summarizes recent research on circRNA's role in CRC, and discusses the potential use of circRNAs as clinical biomarkers for cancer diagnosis and prognosis, as well as therapeutic targets for CRC treatment.